Auditoria Financiera a los Estados Financieros a la Empresa ‘‘MINABRADEC’’, De Riobamba, Período 2022 - Donoso Parra, Katherine Elizabeth (2024)
ABSTRACT: The present research work deals with the financial audit of the financial statements of the company “MINABRADEC” of Riobamba in the year 2022. Its main objective is to evaluate the reasonableness of such financial statements for the aforementioned period. A documentary review of previous research related to the topic was carried out to ensure the relevance of the research and elaborate on the project. In addition, a theoretical framework was developed that includes the fundamental concepts necessary for executing the study. The financial audit of the financial statements of the company “MINABRADEC” Riobamba 2022 yielded significant findings in relation to accounts receivable and inventories. Problems were identified in the management of these accounts, including the need for policies when giving credits and inventories regarding uncontrolled procedures, which the company needs to review its internal control policies and procedures. An uncollectible account in Mina Blade's financial statements indicates the urgent need to review and strengthen the accounts receivable management protocols. In addition, the company must develop strategies to recover any outstanding debt and minimize the negative financial impact on its operation and business reputation.